Unconventional strength training methods to increase athletic performance - Craven, K. T.; Brooks, K. (Journal of Sport and Human Performance, 2013)
Strength training professionals continually develop new training techniques to improve athletic performance. Several unconventional training methods claim to provide strength, power, balance, and conditioning gains that a more conventional program does not. For this review, conventional training methods are defined as basic power lifting or a traditional weight training program. Unconventional training methods will include other non-traditional programs such as junkyard, manual resistance, and modality training. These more unconventional methods show possibility in improving athletic performance and injury prevention.